Memorandum on social insurance and allied services in their bearing on neurotic disorder
1943 1943 1940s 19 pages 16 facilitating re-entry into employment, and these will need co-ordination. The normal method for re-entry via the employment exchange should entail some form of vocational guidance, and a social worker should co-ordinate this with the other methods mentioned, since the whole procedure involves matching what is medically advisable to what is available. It is hard to see how the psychopaths and defectives could be dealt with adequately without spoiling the atmosphere of the training centres, unless there are some "buffer" industries specially developed for these groups — though not exclusively for them. It is better to accept failure in advance for some than to spoil the running of the various normal schemes for training and occupation by including the relatively untrainable. Rehabilitation of "fit unemployables" should follow similar lines to the rehabilitation of other psychiatric cases. A rehabilitation centre might with advantage be set up to deal with the more difficult of these. As soon as possible rehabilitation should be carried out within existing industrial undertakings under the supervision of the staff from the rehabilitation centre that deals with them at an earlier and less employable stage ; such of these persons as are suitable for retraining in skilled trades may be sent to ordinary retraining centres but should be similarly supervised. Psychologists and psychiatrists should assist in sorting the cases for the different types of retraining, and advising on the disposal or handling of those who are not responding. There are many questions in rehabilitation and training which call for the most thorough consideration before any such scheme is finalized. The rights of the individual, and particularly his freedom of choice, must be preserved, consistently with due regard for his obligations to the community, when the decision has to be taken as to what work he will do in future and how he can be made fit to do it. There are other questions of equal importance concerning rehabilitation. But to consider all this in detail would lead beyond the range of the Beveridge proposals ; and it is not in keeping with the restricted intention of this memorandum. MAIN RECOMMENDATIONS. (1) An efficient mechanism to re-establish the unemployed in industry as soon as possible would be the most important factor in alleviating the psychological distress and illness due to "want." The duration of unemployment which may be unavoidable and so, of necessity, "allowed" or "condoned" by the scheme should be less than the period after which active job-hunting leads to a phase of active psychological stress, and should never be long enough for the final apathetic "broken" stage to develop ; studies should be undertaken at a suitable time to determine the usual durations of these periods in England. (2) With full employment and a comprehensive medical service, the so-called unemployable without physical disability will usually be a psychiatric as well as a social problem. (3) If the elderly are to be encouraged to continue at work, their mental as well as their physical suitability must be taken into account, especially for positions of responsibility. 292/847/2/174